"As Black as Ink": A Case of Alkaptonuria-Associated Myelopathy and a Review of the Literature. Issue 1 (1st January 2019) - Donaldson, Callum J.; Mitchell, Stuart L.; Riley, Lee H.; Kebaish, Khaled M.
Abstract : Study Design: Case report and literature review. Objective: To characterize the rare presentation of myelopathy occurring secondary to alkaptonuria and to evaluate the available evidence regarding its treatment. Summary of Background Data: Alkaptonuria is an autosomal recessive genetic condition with an estimated incidence of 1 in 250, 000 to 1 in 1, 000, 000 people. Mutation of the enzyme homogentisate 1, 2-dioxygenase leads to the production of high levels of homogentisic acid, with subsequent deposition in ligaments, cartilage, and menisci. Involvement of the spine is termed "ochronotic spondyloarthropathy, " of which myelopathy is an uncommon presentation. Methods: We present the case of a 57-year-old man with alkaptonuria-associated myelopathy, who underwent surgical decompression. Ten additional cases were identified in the literature by a systematic search of PubMed and Google Scholar. Results: In a patient presenting with myelopathy, alkaptonuria may be suspected because of medical history, family history, symptoms (including darkened urine, pigmented ear cartilage, and sclera), or radiographic changes, such as multilevel disc collapse, progressive wafer-like disc calcification, extensive osteophyte formation, and spinal deformity. The diagnosis can be confirmed by urine homogentisic acid testing. Of the 11 patients presented here or identified in the literature, 2 were treated nonoperatively, 8 were treated with decompressive spinal surgery, and treatment of the myelopathy was not discussed for 1 patient. In all cases in which outcomes were reported, substantial improvement in the patient's condition was seen. Conclusion: Alkaptonuria is a rare cause of myelopathy, but one that clinicians should understand. Although no disease-modifying treatment currently exists for alkaptonuria, the use of symptomatic treatments and, particularly, surgical decompression is recommended to address myelopathy if it develops. Level of Evidence: 4 Abstract : We describe the case of a 57-year-old man who presented with alkaptonuria-associated myelopathy and identify 10 additional cases in the literature. In a patient presenting with myelopathy, alkaptonuria may be suspected because of characteristic symptoms, radiographic findings, and micturition of dark urine. Surgical decompression is recommended to address the myelopathy.